Orçamento participativo e inovação democrática no espaço público local : o caso de Porto Alegre - Santos, Rosa Fátima dos (2004)
The experience of the Participative Budget gained force in the Brazilian scene in the end of years 80 of century XX, as alternative proposal of democratic innovation and popular participation to the neoliberal ideology. The Brazilian State went by deep transformations in the last years due to the changes of paradigms, from interventionist to regulator. These transformations are fruits of the neoliberal doctrine, ratified for the case of the American countries by the Consensus of Washington in 1989. It is in this context that the participative experiences in Brazil had emerged, intending to be a process of increment of the democracy in the local governments, through popular participation in the public administration and elaboration of the budget. For the relevance of the proposal, this study discourses about methodológical aspects of the participative experiences of local public administration, its possibilities and limits and it makes a study of the Porto Alegre case of the Participative Budget, for being the most occurred in course in the country.